Solving Local Violence by Cosmopolitan Democracy Approach (Jurnal Bina Praja, 2016)
The implementation of democracy intensified since the fall of the new order era has some failures. One of the factors is violence phenomena still continue in the region. This study aims to discuss the violence in the region by presenting cosmopolitan democracy as a new design of more humane democracy. In addition, this research method uses library research, because library research can understand the problem in-depth to find the pattern and recommendation from the violence problems which happens in Indonesia. This study uses Hannah Arendt observations on the phenomenon of violence. In addition, the concept of cosmopolitan democracy is referred from Daniele Archibugi, David Held, and Ulrich Beck is presented as a draft of new democracy direction which is more inclusive and humane. The result of this study discloses that the occurrence of incidence is triggered by failed implementation of the democratic system in Indonesia